Hypoxia-associated genes and metabolic abnormalities in peripheral blood mononuclear cells of type 1 diabetes mellitus patients - Wen-biao Ma; Xue-ying Wang; Yuan-yuan Zuo (Hereditas)
Abstract Background Type 1 diabetes mellitus (T1DM) is a chronic autoimmune disorder characterized by insulin deficiency, which causes hyperglycemia and systemic metabolic dysregulation. Methods In this study, we used the gene expression dataset GSE156035 to identify differentially expressed genes (DEGs) between healthy controls and patients with T1DM. Functional enrichment analysis, Gene Ontology analysis, and protein–protein interaction network analysis were employed to identify hub genes. Results We observed significant upregulation and downregulation of DEGs. Upregulated genes were primarily involved in TGF-beta signaling and retinol metabolism, while downregulated genes were associated with MAPK signaling and circadian rhythm pathways. Crucial cellular processes, such as neutrophil activation, defense response to fungi, and neuron differentiation, were highlighted. Hub genes, such as FOS, JUNB, NR4A2, and DUSP1, were identified and showed strong correlations with key signaling pathways. Additionally, elevated levels of angiogenesis, epithelial-mesenchymal transition, and hypoxia in T1DM were indicated, along with significant alterations in metabolite levels, including glucose, leucine, and phenylalanine, and their correlations with hub genes. Conclusion These findings not only identify specific hub genes as key mediators connecting signaling pathways, biological processes, and metabolic changes but also provide novel insights into the pathophysiology of T1DM.